Livable Rental Houses for Factory Workers in Industrial Area - Rahardiyan Ari Wicahyo; Dewi Septanti; Rika Kisnarini (Institut Teknologi Sepuluh Nopember, 2020)
Rental houses as a place to live is a major needs for factory workers. Liveable rental houses can improve the quality of workers life’s in the future, because they have the opportunity to get a livable house in their lives. Therefore, rental houses in industrial areas provided by the private sector for workers should meet livable houses standards. This study was made to determine the feasibility of habitation and evaluate rental housing for workers provided by the private sector, and then formulate the concept of rental houses according to standards or policies for livable houses, the theory of livable houses and the results of research evaluations of rental houses for factory workers in industrial areas. The methods in this research used positivism with primary and secondary data collection techniques through direct observation at the study location, questionnaires for factory workers as tenants, and interviews. who participated in this study were 123 respondents from a total population of 400 units. The concept of decent housing for workers in industrial areas is obtained from the evaluation results of the standard of livable houses, literature studies, and the results of a SWOT analysis. The results of this study, is about the concept of a livable rental houses for workers in an industrial area, including the area of the room in accordance with the provisions of a bunk bed that can occupy four people so that the rental costs can be share by four people, setting the ventilation system with cross ventilation on two sides of the wall for the occurrence of cross ventilation with a ceiling height of 3 meters, the provision of adequate windows for natural lighting during the daytime so as to save electricity consumption. With a air system and good natural lighting will give positive results for the rental house because the house will be far more livable and healthier to live in. This research is expected to be a reference for rental housing owners and the government to make the concept of livable rental housing for workers in industrial areas.